Challenges of passenger and freight transportation in mega-city regions: A systematic literature review. (December 2022) - He, Zhangyuan; Liu, Qiyang; Zhao, Pengjun
Highlights: Lacking effect analysis of mega-city region's formation on integrated transport system. Effects of freight transport on spatial structure of mega-city region remain unclear. Limited discussion on use of emerging vehicles in mega-city region. Few focus on the integration of passenger and freight transport in mega-city region. Abstract: The mega-city region was projected as the future outcome of the urbanization process, which is commonly composed of single or multiple main cities and peripheral cities through highly developed transportation networks. Because passenger and freight systems commonly share a physical transport network, the effects of urban morphology changes act on both systems at the same time. Although passenger and freight transport in mega-city regions have been addressed in a growing number of journal publications, an overview of research focusing on both topics together is still lacking. Meanwhile, the potential crossed topics between both systems in mega-city regions were limited in the discussion. This situation may hinder local authorities in the formulation of an appropriate transportation agenda for the promotion of collaboration among the transport system between different cities in mega-city regions, even further aggravate the problem of land-use conflict between city and transport, the unreasonably distributed transport infrastructure, and the excessive allocation of transportation resources, etc. Therefore, it's essential to understand the state-of-the-art in the field of passenger and freight transport in the mega-city regions, and to further analyze the potential crossed topics between the two topics. To this end, this paper adopts a systematic literature review method, covering 468 papers and research works published from 2016 to 2021. The cross-relevance analysis shows that, thus far, only seven crossed topics have covered passenger and freight transport simultaneously, while five potential topics can be further studied. Finally, four research gaps have been identified to which scholars could be encouraged to contribute.